Imaging surprise: Incidentally detected duplication of gall bladders in a case of ruptured liver abscess: A rare case report - Kaustubh Gupta, MD; Priya Das, MBBS; Gaurav Raj, MD; Vikas Singh, MS (Radiology Case Reports)
Anatomical variations of the biliary tree are common and frequently encountered during imaging; however, anatomical variations of the gall bladder are rare. Information about such rare variant anatomy must be communicated to the surgeon beforehand due to the risk of common bile duct (CBD) and hepatic artery injury during surgery. Duplication of the gall bladder is a rare malformation and may be asymptomatic or symptomatic, with symptoms being difficult to differentiate from single gall bladder pathology. Imaging plays a pivotal role in preoperative planning.